Determining the basic parameters of one-sided thermal inspection for separation in glass-fiber-reinforced plastic partsl - Storozhenko V. A. (1978, 1978)
The two-dimensional problem of the active thermal inspection by a moving heat beam is solved. Relationships are obtained for the temperature differential and the temperature constant to the parameters of the defect and the time and rate of inspection. A comparison is made of the results of experimental and theoretical investigations.